2018
DOI: 10.1111/ajd.12982
|View full text |Cite
|
Sign up to set email alerts
|

The Melanocortin 1 receptor and its influence on naevi and melanoma in dark‐skinned phenotypes

Abstract: It is well appreciated that melanocortin 1 receptor variants can produce a fair skinned and red-haired phenotype that has a strong association with increased melanoma risk. These patients are easily recognised and given appropriate attention. What may not be appreciated is that darker-skinned individuals may also carry melanocortin 1 receptor variant alleles and that they can also be at increased risk of melanoma. Considering that melanocortin 1 receptor is crucial for melanocyte proliferation, regulation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Additionally, it is known that various high, moderate, and low‐risk germline polymorphisms and candidate single nucleotide polymorphisms (SNPs) influence the susceptibility and prognosis in cutaneous melanoma 23 . It is thought that melanocortin 1 receptor variants may have an effect on both melanoma development and the number and morphology of nevi regardless of phenotype 24 . Recent studies have shown that low‐penetrance melanoma susceptibility genes or SNPs and MITF E318K variants are not only indicators of high melanoma risk, but they also influence nevus count 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is known that various high, moderate, and low‐risk germline polymorphisms and candidate single nucleotide polymorphisms (SNPs) influence the susceptibility and prognosis in cutaneous melanoma 23 . It is thought that melanocortin 1 receptor variants may have an effect on both melanoma development and the number and morphology of nevi regardless of phenotype 24 . Recent studies have shown that low‐penetrance melanoma susceptibility genes or SNPs and MITF E318K variants are not only indicators of high melanoma risk, but they also influence nevus count 25 .…”
Section: Discussionmentioning
confidence: 99%
“…23 It is thought that melanocortin 1 receptor variants may have an effect on both melanoma development and the number and morphology of nevi regardless of phenotype. 24 Recent studies have shown that low-penetrance melanoma susceptibility genes or SNPs and MITF E318K variants are not only indicators of high melanoma risk, but they also influence nevus count. 25 Based on this information, we argue that there is a strong correlation between melanoma and nevus count, not because melanoma arises on a preexisting nevus but because they share a common genetic basis.…”
Section: Discussionmentioning
confidence: 99%
“…This is most strongly expressed in the red hair phenotype with its extreme sensitivity to UV exposure 21 . It has been shown that in the Australia approximately 50% of the population carry at least one of these dysfunctional MC1R genes making sun exposure pattern choices and protective measures vital to maintaining good health 22 . Both MC1R and ET-1 influence localisation of XPA, in nuclear and chromatin fractions, on UV exposure.…”
Section: Dna Damage Response In Melanocytesmentioning
confidence: 99%